Business plan- bilingue theme bar (2017)
This business plan is made with the purpose of presenting it to potential investors in business rounds and/or venture capital funds proposed by the Government within its national development plan. A business oportunity regarding the creation of a theme bar in Bogota that encourages bilingualism is considered is this document. Said idea arises in the formation process of the Modern Languages major as ECCI University students. There is a law in Colombia, the 1014 2006, the Promotion of a Culture of Entrepreneurship ,that seeks to encourage the development of innovative business ideas that motivate the creation of companies to sustain the economy, from educational establishments. Entrepreneurship is a way of thinking, reasoning, and acting focused on opportunities, outlined with a global vision and carried out through a balanced leadership and the management of a calculated risk which result is the creation of value that benefits the company, the economy and society.